Analisis Kendala Praktikum Biologi di Sekolah Menengah Atas: (Obstacles Analysis of Biology Laboratory Practice of High School) - Nur Rahmah; Iswadi Iswadi; Asiah Asiah; Hasanuddin Hasanuddin; Devi Syafrianti (BIODIK, 2021)
This study aims to determine the completeness of laboratory facilities and infrastructures, the implementation of the laboratorial practice, to measure the causal factors of laboratorial practice to run, and to be alert of laboratory infrastructure completeness and the implementation of the biology laboratorial practice. Data were collected by observation and questionnaires. The sample in this study were 11 high schools in Banda Aceh, with respondents 11 biology teachers who are responsible for teaching class XI and 99 students of class XI IPA. The data were analyzed using the proportion formula and the product moment answer formula. The study resulted in the findings that: 1) the proportion of completeness of facilities and infrastructure was 66.77% (good). 2) the proportion of laboratorial ptactice implementation was 62.81% (sufficiently implemented). 3) factors of laboratorial procurement, including, inadequate support, inadequate materials, insufficient time allocation, lack of readiness of laboratory assistants in preparing tools and materials, absence of laboratory assistants in several sample schools, and some biology / laboratory assistants in The sample school had never been trained to guide students or to use laboratory equipment. 4) the correlation between the laboratory facilities completeness and infrastructure with laboratorial practice implementation was 0.27 (low). Abstrak. Penelitian ini bertujuan untuk mengetahui kriteria kelengkapan sarana dan prasarana laboratorium, kriteria keterlaksanaan praktikum, mengumpulkan faktor kendala yang menyebabkan kurang berjalannya praktikum, dan untuk mengetahui korelasi antara kelengkapan sarana prasarana laboratorium dengan keterlaksanaan praktikum biologi. Pengumpulan data dilakukan dengan cara observasi dan angket. Sampel dalam penelitian ini adalah 11 SMA di Kota Banda Aceh, dengan responden 11 guru biologi yang mengajar kelas XI dan 99 peserta didik kelas XI IPA. Data dianalisis dengan menggunakan rumus persentase dan rumus korelasi Product moment. Hasil penelitian diketahui bahwa: 1) persentase kelengkapan sarana dan prasarana laboratorium sebesar 66,77% (baik). 2) persentase keterlaksanaan praktikum sebesar 62,81% (cukup terlaksana). 3) faktor kendala pelaksanaan praktikum diantaranya, fasilitas pendukung yang tidak memadai, minimnya kelengkapan bahan praktikum, alokasi waktu untuk praktikum tidak mencukupi, kurangnya kesiapanÂ  laboran dalam mempersiapkan alat dan bahan praktikum, tidak adanya laboran di beberapa sekolah sampel, dan sebagian guru biologi/laboran di sekolah sampel belum pernah mengikuti pelatihan mengenai praktikum atau penggunaan alat laboratorium. 4) korelasi antara kelengkapan sarana dan prasarana laboratorium dengan keterlaksanaan praktikum sebesar 0,27 (rendah).